Patterns of long-term swallowing dysfunction after definitive radiotherapy or chemoradiation. Issue 1 (October 2015) - Christianen, Miranda E.M.C.; Verdonck-de Leeuw, Irma M.; Doornaert, Patricia; Chouvalova, Olga; Steenbakkers, Roel J.H.M.; Koken, Phil W.; René Leemans, C.; Oosting, Sjoukje F.; Roodenburg, Jan L.N.; van der Laan, Bernard F.A.M.; Slotman, Ben J.; Bijl, Hendrik P.; et al.
Abstract: Objectives: To identify patterns of long-term, radiation-induced swallowing dysfunction after definitive radiotherapy with or without chemotherapy (RT or CHRT) and to determine which factors may explain these patterns over time. Material and methods: The study population consisted of 238 consecutive head and neck cancer patients treated with RT or CHRT. The primary endpoint was ⩾grade 2 swallowing dysfunction at 6, 12, 18 and 24 months after treatment. Cluster analysis was used to identify different patterns over time. The differences between the mean dose to the swallowing organs at risk for each pattern were determined by using dose maps. Results: The cluster analysis revealed five patterns of swallowing dysfunction: low persistent, intermediate persistent, severe persistent, transient and progressive. Patients with high dose to the upper pharyngeal, laryngeal and lower pharyngeal region had the highest risk of severe persistent swallowing dysfunction. Transient problems mainly occurred after high dose to the laryngeal and lower pharyngeal regions, combined with moderate dose to the upper pharyngeal region. The progressive pattern was mainly seen after moderate dose to the upper pharyngeal region. Conclusions: Various patterns of swallowing dysfunction after definitive RT or CHRT can be identified over time. This could reflect different underlying biological processes.